Placing Robert Hughes: A promissory note - Beilharz, Peter (2013)
The recent, premature death of art critic Robert Hughes registered significant celebrity attention, but little for the extent and depth of his intellectual achievement. Hughes called himself a writer, or else a journalist. He had at least two especial qualifications, in this capacity. He had an Eye, but he also had a Voice. He was a brilliant, if sometimes prolix, writer and presenter. He was a performer, and his work should be seen as performance. This essay, offered as a promissory note, seeks to place Robert Hughes in terms of style and substance but also in terms of centre and periphery, in terms of the cultural traffic between them. It touches on three aspects of his reception. First, on the obituaries, which sought largely to reclaim his body as Australian, even after 50 years of absence. Second, on The Fatal Shore and its reception, itself indicative of the difficulty in neatly placing Hughes in terms of nationalist conceptions. Third, it discusses leading critical interpretations, asking for more, please, and promising to help contribute to the appreciation of Hughes as Tory radical stylist and contrarian. © The Author(s) 2013.